ANALISIS PERSEDIAAN BAHAN BAKU KACANG KEDELAI DALAM PEMBUATAN KECAP MENGGUNAKAN METODE EOQ DI PABRIK KECAP SEGI TIGA KABUPATEN MAJALENGKA - Saeful Anwar, Budi; Alamsyah P, Agus; Kusumadewi, Intan (Universitas Majalengka, 2019)
Factory Segi Tiga is a company engaged in the industry that is producing soy sauce, in carrying out its production it is closely related to row materials which are important components that must be available in the production prosess, the row material used is soybeans. This study aims to determine the control of soybean row material supplies at the factory Segi Tiga use EOQ method. From the results of calculations that have been done now apply in the company by EOQ method in controlling row materials, it can be concluded that using the EOQ method results more efficiently this can be seen by the number of purchases averaging 6087,5 kilograms in one number of orders 8 times a year and inventory costs amounting to Rp 4.889.494,- in one order, whereas if you use the EOQ method the number of orders in one message is 18.768 kilograms whit the number of orders 3 times a year whit the amount of expenses incurred is Rp 2.870.776,6 in one order. To anticipate things you don’t want related to row material inventories. The EOQ method advises the factory to provide safety supplies of 4963,4 kilograms and order row materials again when the row material is 487 kilograms, with this EOQ method can avoid the delay in the supply of raw materials because the supply of raw materials can be sure to be constant and compatible with the lead time, then to reach the factory research allowance you should use the EOQ method.